Strategi Komunikasi Yesus dengan Perempuan Samaria Menurut Yohanes 4:7-26 dan Implikasinya dalam Pengajaran Injil Kontemporer - Kumoro Adiatmo; Simon (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
This research examines Jesus' interaction with the Samaritan woman as recorded in the John 4:7-26, focusing on Jesus' communication techniques and their relevance for contemporary evangelism and Christian teaching. In this dialogue, Jesus combines empathy and inclusivity to reach out to the woman, transcending ethnic and religious boundaries through the use of the